Melihat Keikutsertaan Suami dalam Program Keluarga Berencana di Kecamatan Banda Sakti Kota Lhokseumawe - Novika Rahmayanti; Muhammad bin Abubakar; Muhammad Akmal (Journal of Governance and Social Policy, 2022)
The participation of men in the Family Planning (KB) program, especially the use of contraceptives in Banda Sakti District, Lhokseumawe City is still very low. The purpose of this study was to determine what factors influence men's participation in the family planning program in Banda Sakti District, Lhokseumawe City. The research design used a cross-sectional approach to 66 respondents obtained through simple random sampling technique. The results showed a significant relationship between service quality factors (p value = 0.003, OR = 11.200), knowledge (p value = 0.009, OR = 14.385) and culture (p value = 0.000, RO = 13.300) with male participation in family planning programs. There is no significant relationship between socio-demography (education, income and number of children) and access to services with male participation in family planning in Banda Sakti District, Lhokseumawe City. To increase participation, appropriate methods are needed, especially for conveying information on condom and vasectomy programs as well as increasing family planning promotion through media with attractive packaging variations so that knowledge about contraception increases. And also increase socialization about equality in the use of contraception, not always the wife, husband must also participate as a family planning acceptor.